PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN, DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PARUH WAKTU PADA CV. KARYA GEMILANG “NCO EVENT ORGANIZER” - Arya Munang Ayu Heny Ratna Dewi; I Nengah Suardhika; I Gede Yudhi Hendrawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Success in the company is determined by the achievement of good performance results by employees. Human resources in a company greatly affect the company's performance, because if the human or employee's performance is good, then the company's performance will be good. Conversely, if the performance of people or employees in a company decreases, the company's performance will also decline. This study aims, to determine and explain individual characteristics, job characteristics and organizational climate on the performance of part-time employees at CV. Karya Gemilang